2020
DOI: 10.3390/microorganisms8101567
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urban Wastewater in the Environmental Transmission of Antimicrobial Resistance: The Current Situation in Italy (2010–2019)

Abstract: Scientific studies show that urban wastewater treatment plants (UWWTP) are among the main sources of release of antibiotics, antibiotic resistance genes (ARG) and antibiotic-resistant bacteria (ARB) into the environment, representing a risk to human health. This review summarizes selected publications from 1 January 2010 to 31 December 2019, with particular attention to the presence and treatment of ARG and ARB in UWWTPs in Italy. Following a brief introduction, the review is divided into three sections: (i) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…Real-time RT-(q) PCR analysis was performed as described in La Rosa et al [ 19 ]. Briefly, each 25 μL reaction contained 5 μL of RNA, 12.5 μL of 2× reaction buffer provided with the AgPath-ID™ One-Step RT-PCR reagents (Applied Biosystems, Foster City, CA, USA, 1 μL of 25× RT-PCR enzyme mix, 1 μL of forward primer (12.5 μM), 1 μL of reverse primer (22.5 μM), 1 mL of probe (6.25 μM), 1.83 μL of nuclease-free water (not DEPC, diethylpyrocarbonate-treated), and 1.67 μL of detection enhancer for real-time PCR (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time RT-(q) PCR analysis was performed as described in La Rosa et al [ 19 ]. Briefly, each 25 μL reaction contained 5 μL of RNA, 12.5 μL of 2× reaction buffer provided with the AgPath-ID™ One-Step RT-PCR reagents (Applied Biosystems, Foster City, CA, USA, 1 μL of 25× RT-PCR enzyme mix, 1 μL of forward primer (12.5 μM), 1 μL of reverse primer (22.5 μM), 1 mL of probe (6.25 μM), 1.83 μL of nuclease-free water (not DEPC, diethylpyrocarbonate-treated), and 1.67 μL of detection enhancer for real-time PCR (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To date, wastewater monitoring has been implemented as a successful strategy to track other health-related chemical and biological biomarkers, for example, in relation to illicit drug consumption, pharmaceutical use/abuse, water pollution, and the occurrence of antimicrobial resistance genes [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that most sulfa-degrading bacteria may be resistant to sulfonamides and may carry sulfonamide resistance genes including sul1 and sul2 (Vila-Costa et al 2017). Many studies have focused on Escherichia coli because it is considered to have both the ability to indicate fecal contamination and the ability to assess the spread of antibiotic resistance in water environment (Triggiano et al 2020). Such indicator microorganisms, especially the coexistence of coliform and potential pathogens, may promote the transfer of ARGs to potential pathogens and further increase the risk of MDR pathogens (Mishra et al 2018).…”
Section: Host Identi Cation Of Argsmentioning
confidence: 99%
“…Furthermore, although coliforms has been established as sanitary standards of the safety of fresh water, it is shocking that the problem of multiple drug resistance was on the rise (Mishra et al 2018). Coliforms are extremely receptive and altruistic to horizontal gene transfer in nature, so it is easy to become a hot spot to accept and spread antibiotic resistance genes in the environment (Triggiano et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ciprofloxacin (a fluoroquinolone) and cefalexin (a β-lactam) have been recently proposed as markers of antibiotic pollution in environmental water and municipal wastewater treatment plant effluents [3]. Nowadays, it is well-known that the continuous input of antibiotics into municipal wastewater treatment plants and environmental water becomes a risk factor for resistant bacteria proliferation [4][5][6]. Bacterial resistance to antibiotics represents a great threat to human health [7].…”
Section: Introductionmentioning
confidence: 99%